Social epigenetics: a science of social science?. Issue 1 (21st April 2016) - Chung, Emma; Cromby, John; Papadopoulos, Dimitris; Tufarelli, Cristina
Abstract: Epigenetics has considerable potential to transform social science by embedding mutually regulative reciprocal connections between biological and social processes within the human activities it studies. This paper highlights common epigenetic methods and outlines practical considerations in the design of 'social epigenetics' research addressing the identification of biomolecular pathways, statistical inference of causality, conceptualization of the environment as a biochemical event, heritability of epigenetic alterations and intergenerational accountability, and concept of time implied by attempts to capture complex, non‐linear gene‐environment interactions. Finally, we reflect on the social epigenome as a conceptual space and try to identify barriers to translation, and practical and ethical issues raised by epigenetics research. In order for social epigenetics and social science to contribute to the emergence of this putative 'science of social science' and to capture meaningful human experience they will both need to change significantly.